Product repair support system, product manufacturing system, and product manufacturing method - SOGA AKIRA (2008)
A product repair support system is configured to support repair of a product rejected in an inspection based on a prescribed inspection standard. The product repair support system includes: repair information storage part; reference information storage part; and repair condition optimization part. The repair information storage part is configured to store a result of the inspection of the repaired product as repair information. The reference information storage part is configured to store reference information related to the product. The repair condition optimization part is configured to determine appropriateness of a repair condition or selection of the repair condition on basis of the repair information and, in response to a determination of being inappropriate, to optimize data of the repair condition or the selection on basis of at least one of the repair information and the reference information.